Phenotypic traits differentiating the genetic resources of pea (Pisum sativum L.) by the type of use - E. V. Semenova; A. P. Boyko; L. Y. Novikova; M. A. Vishnyakova (Вавиловский журнал генетики и селекции)
The paper presents an analysis of the data obtained for pea accessions from the VIR collection studied at the Adler Experiment Station in the setting of the Krasnodar Territory in 2017–2019. It was for the first time that these accessions were studied for a set of phenotypic traits. The object of the study was a sample of 494 pea accessions originated from 43 countries and 18 regions and territories of the Russian Federation. The work was carried out in compliance with the methodological guidelines developed at VIR. Statistica 13.3 software was employed for statistical data processing. An assessment of four qualitative, 10 quantitative and four phenological traits in the accessions made it possible to differentiate them by the type of use, that is, as dry, forage and garden peas. The varieties differing in the type of use significantly differed by the values of such traits as stem length, number of pods per plant, number of nodes to the first flower, number of flowers in the inflorescence, the maximum number of seeds per pod, pod length, and a narrower pod of forage pea compared to that of dry and garden peas. The average values of these traits were recorded for the peas with different types of use. The maximum difference was noted between garden and forage pea varieties. Dry pea varieties occupied an intermediate position. The complex of phenotypic traits identified determines the differences between three types of pea use, which is important when selecting the initial material for breeding appropriate varieties.